You could express it as cotx + tanx if you wanted
Whether or not that is a simplification is a matter of point of view.
2007-03-10 10:27:11
·
answer #1
·
answered by gandalf 4
·
0⤊
0⤋
Reduce the fractions to the same denominator
cosx/sinx + sinx/cosx = (cos^2x + sin^2x)/sinxcosx = 1/sinxcosx , since cos^2x + sin^x = 1
You can reduce further using sin2x = 2 sinxcosx in the donominatos to obtain finally
1/sinxcosx = 2/sin2x
2007-03-10 10:20:23
·
answer #2
·
answered by physicist 4
·
0⤊
0⤋
Cosx/Sinx +Sinx/Cosx
=Cosx(cosx) + Sinx(sinx)/Sinxcosx
=Cos^ x +Sin^x / Sinxcosx
=1/SinxCosx
=Cosecx .Secx
2007-03-10 16:21:30
·
answer #3
·
answered by ash 2
·
0⤊
0⤋
Find the common denominator.
(cosx/sinx)(cosx/cosx)
+(sinx/cosx)(sinx/sinx)
(cos^2x+sin^2x)/(sinxcosx)
The numerator simplifies to 1
according to the pythagorean identity.
The denominator simplifies to .5sin(2x).
1/(.5sin(2x))
=2csc(2x)
2007-03-10 10:20:30
·
answer #4
·
answered by Tim 2
·
0⤊
0⤋
= (cos²x + sin²x) / (sinx.cosx)
= 1 / sin x. cos x
= 2 / 2.sinx.cosx
= 2 / sin 2x
2007-03-10 10:21:31
·
answer #5
·
answered by Como 7
·
0⤊
0⤋